Further Results on Uniqueness of Meromorphic Functions concerning Fixed Points - Xiao-Bin Zhang (Abstract and Applied Analysis)
We will study the uniqueness problems of meromorphic functions of differential polynomials sharing fixed points. Our results improve or generalize some previous results on meromorphic functions sharing fixed points.